Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Variasi Menu Terhadap Kepuasan Konsumen Di Warung UMKM Minas Syukur Kambang - Waifa Nuraprilia; Sissah Sissah; Marissa Putriana (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
Micro, Small and Medium Enterprises (MSMEs) are productive businesses owned by individuals or business entities that meet the criteria for being a micro enterprise. In doing business, the goods sold must have consistency and quality that is in accordance with what is advertised. Assuming that his character is good, buyers will make repeat purchases more often at Minas Syukur Kambang. The quality of the products at Minas Syukur Kambang is good but the quality of service is still lacking because there are still many miscommunications. The menu variations are also good with various variations with different flavors, but sales results fluctuate even though if all the product indicators had been implemented, it could have encouraged consumer interest in buying the product, thereby increasing sales results. The research aims to determine the influence of product quality, service quality, menu variations on consumer satisfaction in the Minas Syukur Kambang UMKM. The research method uses a quantitative descriptive sample taken as many as 95 respondents using a simple random sampling technique, namely a random sampling technique, namely a sampling technique where all individuals in the population, either individually or together, are given the same opportunity to be selected as sample members. The results of this research state that product quality has a positive effect and service quality does not have a positive effect on consumer satisfaction. Meanwhile, menu variations have a positive effect on consumer satisfaction. Based on data analysis in this research, these variables are valid and reliable. In testing the classical assumptions, this research has a normal distribution, heteroscedasticity and multicollinearity do not occur.